Understanding Violent-Crime Recidivism - Prescott, J.J. (2020)
People convicted of violent crimes constitute a majority of the imprisoned population but are generally ignored by existing policies aimed at reducing mass incarceration. Serious efforts to shrink the large footprint of the prison system will need to recognize this fact. This point is especially pressing at the time of this writing, as states and the federal system consider large-scale prison releases motivated by the COVID-19 pandemic. Those convicted of violent crimes constitute a large majority of older prisoners, who are extremely vulnerable to the spread of the virus behind bars. Excluding them from protective measures will deeply undermine those measures’ effectiveness—and yet many governors and officials have hesitated due to fears of violent-crime recidivism. In addition, the population imprisoned for violent offenses also exhibits sharper demographic disparities than the general prison population across both age and race. Consequently, reforms that target those convicted only of nonviolent crimes will likely exacerbate existing inequalities in the criminal justice system. In this Article, we start from the premise that better understanding individuals convicted of violent crimes is essential to overcoming resistance to the idea of releasing them earlier—and in particular, to address the fear that this population will almost certainly reoffend violently. We review existing studies and offer new empirical analysis to inform these questions. Although estimates vary, our synthesis of the available evidence suggests that released violent offenders, especially homicide offenders who are older at release, have lower overall recidivism rates relative to other released offenders. At the same time, people released after previous homicide convictions may be more likely to commit new homicides than otherwise comparable releasees, although probably not by as much as most would expect